Comparación de protocolos de bioindicadores y su eficacia en la medición de la calidad del agua en los ríos: Quevedo, San Pablo, Lulo y Estero La Cadena. Año 2012. Plan de difusión. - Gutiérrez Lara, Víctor Eduardo (2013)
The use of bioindicators of water is being proposed as a new tool to determine the quality of aquatic ecosystems, this does not mean to displace traditional methods such as physical-chemical analysis of water. Its use greatly simplifies the field and laboratory activities, since its application only requires the identification and quantification of organisms based on diversity indices and adjusted sensitivity ranges that qualify the category of water quality. In this study it was our objective to compare the protocols IBF, ETP, Alpha and BMWCR as bioindicators of water quality in rivers Quevedo, San Pablo, Lulo and Estero La Cadena. Apart from this specific point or goal, the research proposes Identify macroinvertebrates present in these aquatic ecosystems that characterize the area sections of rivers and estuaries. The hypothesis of this research was that all protocols are equal bioindicators of water and apply to rivers and estuaries for measuring water quality but their procedures are costly and are not identical and applicable to our rivers and streams. The best plan for dissemination of ETP protocol as bioindicator of water quality in rivers and estuary is an excellent alternative proposal put forward in this research, as it will help many professionals (environmentalists and engineers) devoted to the study of water quality using this new technique.